As mulheres no processo de colonização do oeste catarinense: invisibilidade e resistência (1920/1960) - Signori, Andréia Aparecida (2018)
This dissertation deals with women in the process of colonization of the West of Santa Catarina from 1920 to 1960, addressing the context of colonization, invisibility and resistance of women in this process. The construction of the scenario in which the colonization occurred is based on bibliographies of regional history and through documents from the family collection of my great-grandmother Elvira Laura, one of the migrant women who participated in the colonization of the region. Historiography on the colonizing process is usually placed under a patriarchal bias where women were invisibilized, they barely appear in the representations and memories of colonization. In the light of Thompson's theoretical reference from history viewed from below, research works on the participation of women in the colonizing process. Laws as well as religion and customs have created patterns of subordination and silencing for women. It was customary to nominate women as household professionals, an unprofessional activity, and even when they had other trades, they were not recognized. By means of the customs the idea of inferiority of the women was consolidated, because, the right of inheritance was denied to them. To understand the context of male domination, Pierre Bourdieu is the theoretician who supports research. Christianity contributed to the standards of morality where being a mother and being modest implied submission and obedience. Looking at old sources with a new look, it is possible to identify that, although so many forces contributed to the silence of women in the colonization history of the West of Santa Catarina, many of them resisted and became visible, challenged established standards, refused to submit and carried out their identities, their professions and their rights. The theoretical support of Mary Del Priore contributes to understand and better historicize the protagonism and resistance of women in the process of colonization of the West of Santa Catarina present in the photographs and judicial processes of the time.